2009
DOI: 10.1103/physrevd.80.094013
|View full text |Cite
|
Sign up to set email alerts
|

Factorization structure of gauge theory amplitudes and application to hard scattering processes at the LHC

Abstract: Previous work on electroweak radiative corrections to high-energy scattering using soft-collinear effective theory (SCET) has been extended to include external transverse and longitudinal gauge bosons and Higgs bosons. This allows one to compute radiative corrections to all parton-level hard scattering amplitudes in the standard model to next-to-leading-log order, including QCD and electroweak radiative corrections, mass effects, and Higgs exchange corrections, if the high-scale matching, which is suppressed b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
164
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(167 citation statements)
references
References 99 publications
(351 reference statements)
3
164
0
Order By: Relevance
“…In recent years we have seen significant progress towards determining the singularities of multi-leg amplitudes with general kinematics beyond the planar limit and beyond one loop [4,19,20,[25][26][27][28][29][30][31][32][33][34]41]. Complete two-loop results are now available for the soft anomalous dimension in both the massless and massive cases.…”
Section: Jhep04(2014)044mentioning
confidence: 97%
“…In recent years we have seen significant progress towards determining the singularities of multi-leg amplitudes with general kinematics beyond the planar limit and beyond one loop [4,19,20,[25][26][27][28][29][30][31][32][33][34]41]. Complete two-loop results are now available for the soft anomalous dimension in both the massless and massive cases.…”
Section: Jhep04(2014)044mentioning
confidence: 97%
“…[73][74][75], relevant to the Drell-Yan process), and exist even in inclusive cross sections due to the fact that the initial states that are not electroweak singlets [76][77][78][79]. The form of these logarithms, and their resummation, can differ process-to-process, and requires careful treatment of the real electroweak radiation to ensure proper cancellation with numerically large contributions from virtual corrections (see, e.g., [80][81][82][83][84] for a general discussion of EW Sudakov logarithms in virtual corrections, or ref. [85] for a recent study on a set of specific processes).…”
Section: Theory Predictionsmentioning
confidence: 99%
“…Resummation of the EW Sudakov logarithms will bring perturbative stability to the cross section, and in refs. [82,83] it was suggested that this resummation along with QCD corrections can achieve a scale uncertainty within 1%. Hence, while these corrections are numerically important, resummation of these effects will give a well-controlled theoretical prediction for the EW corrections, and one expects small uncertainties on the result.…”
Section: Jhep02(2015)007mentioning
confidence: 99%
“…Processes with four hard partons in QCD separate into a number of color structures, corresponding to separate operators in SCET, which mix under RG evolution. Similar color mixing has already been studied for collinearlyregulated soft Wilson lines using the traditional approach to resummation [19], and for quark scattering [15], gauge boson production [20] and tt production [6] using SCET. For NNLL resummation, the renormalization group equations must be solved to least 2-loop order.…”
mentioning
confidence: 99%
“…For NNLL resummation, the renormalization group equations must be solved to least 2-loop order. A general form for these RGEs is known [20,21,22,23,24,25], as is the related soft function evolution equation [19].…”
mentioning
confidence: 99%